A STUDY OF FILLERS UTTERED IN ENGLISH PUBLIC SPEAKING - Firiady, Maryska; Mahendra, Aloisius Wisnu (ELTR Journal, 2019)
In the formal context of communication, capability to speak in public and convince the audiences becomes an essential necessity (Al-Tamimi, 2014). Nevertheless, many people are afraid of public speaking (Brewer, 2001). As a result, fillers such as err…, umm…, or well, so, you know, I mean are often produced. However, fillers are considered as additional utterances produced by speakers to communicate naturally with the listeners. They help the speakers to shift one idea to another to make the listeners understand the meaning conveyed by the speakers easily. This study investigated twenty English public speaking videos and looked for the variation of fillers uttered by the speakers. The results showed that so, err, and umm were the frequent fillers uttered. The use of these fillers had various functions such as to introduce the speaker’ ideas, to gain audience’s attention, or to give time for the speakers to search for the word.